A Single Dose, Bioavailability Study Mounjaro (Tirzepatide) Solution for Injection in a Pre-Filled Pen 2.5 Mg/0.5 Ml in Normal Healthy Adult Human Subjects Under Fasting Condition - Arumugam, Arjun; Lakshmi, Geetha; Srinivas, G; Rao, Nageswara (European Journal of Applied Sciences, 2025)
Background: Tirzepatide is a novel long-acting agonist of the gastric inhibitory polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) receptors, exhibiting high selectivity for both human receptors. Its pharmacological profile includes a strong affinity for both the GIP and GLP-1 receptors, which are pivotal in the regulation of glucose homeostasis and appetite control. Notably, the activity of Tirzepatide at the GIP receptor closely mimics that of the endogenous GIP hormone, facilitating insulin secretion in a glucose-dependent manner. In contrast, its action at the GLP-1 receptor is somewhat reduced when compared to the native GLP-1 hormone. Both receptors are widely distributed throughout the body, being present on pancreatic α and β cells, as well as in the heart, vasculature, immune cells (such as leukocytes), gastrointestinal tract, and kidneys. Additionally, GIP receptors are localized to adipocytes, emphasizing their role in lipid metabolism and energy balance. Importantly, both GIP and GLP-1 receptors are expressed in brain regions integral to appetite regulation, suggesting a complex interplay between these pathways and body weight management. The primary objective of this study was to evaluate the pharmacokinetics and bioavailability of tirzepatide following subcutaneous administration in healthy subjects. Moreover, the impact of tirzepatide on weight reduction was assessed by comparing the subjects’ weight measurements taken at study check-in and again at the end of the intervention period. Materials and methods: Materials: Dose and Mode of Administration: Mounjaro (Tirzepatide) solution for injection in a prefilled pen 2.5 mg/0.5 mL, subcutaneous injection in sitting posture under fasting condition. Methods and Findings: The study was conducted as a single-dose bioavailability study under fasting conditions to evaluate the pharmacokinetics of Tirzepatide. A total of four male subjects, aged between 31 and 40 years, who met the protocol defined eligibility criteria were enrolled in the study after a written informed consent was obtained. Each participant was administered with a single dose of subcutaneous injection of Tirzepatide, administered in the right side of abdomen to ensure standardisation for consistent bioavailability and pharmacokinetic profiling. Blood samples were collected at various time points, up to 96 hours post-administration, enabling a comprehensive analysis of the drug’s pharmacokinetic parameters. To evaluate safety, thorough assessments were conducted prior to enrolment in study, during the study and post study, including clinical examinations, vital sign measurements, laboratory tests, and close monitoring of each subject’s overall well-being during the conduct. Any symptoms or signs of adverse events were carefully evaluated throughout the study duration and documented. The plasma concentrations of Tirzepatide were quantified using a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method, ensuring reliable and accurate measurement of the drug concentration levels. The concentration data obtained were then used for pharmacokinetic analysis using the Phoenix WinNonlin version 8.4 software tool. Conclusion: The study was conducted to evaluate the bioavailability and pharmacokinetic profile of Tirzapatide, a novel long-acting agonist of GIP and GLP-1 receptors, when a single dose is administered via subcutaneous route to healthy male subjects. The findings from this study will contribute to the understanding and provide insights into Tirzepatide’s therapeutic efficacy in weight reduction and its safety profile.